Preferences for healthcare chaplaincy services among U.S. adults: differences by inpatient and outpatient settings. Issue 2 (3rd April 2023) - Rajaee, Geila; Patel, Minal R.
Abstract: We examined preferences around spiritual support services delivered by chaplains among U.S. adults in outpatient and inpatient healthcare settings using a cross-sectional national survey of U.S. adults ( n  = 1, 020). For outpatient settings, 5% reported interest in chaplain services, whereas 16% reported interest in inpatient settings. In both settings, a higher perceived value of chaplain services ( p  < 01) and previous experience with a chaplain ( p < .01) were associated with a greater interest in a chaplain consult when adjusting for demographic factors. In both settings, the most desired services were to explore what was most important in the event of a serious illness or injury (46–47%), values related to treatment decisions (43–46%), and connecting to resources for personal strength and resilience (36–39%), whereas exploring more religious concerns was less desirable. There is a need to identify the role of chaplains within the context of healthcare to meet patients' desire for specific services.